The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3354/meps10257
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotope fractionation in amino acids from harbor seals: implications for compound-specific trophic position calculations

Abstract: Compound-specific isotope analysis of individual amino acids (AA) is a rapidly growing tool in ecological studies to assess diet and trophic position (TP) in both modern and ancient foodwebs. We conducted the first controlled feeding study examining δ 15 N values in AAs in a marine mammal (harbor seal Phoca vitulina). The pattern of δ 15 N variation among AAs in seals was similar to that observed in other heterotrophs, although exceptions were found with proline and threonine. However, many δ 15 N changes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
252
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(280 citation statements)
references
References 42 publications
(131 reference statements)
27
252
1
Order By: Relevance
“…Underestimated TPs based on CSIA‐AA have also been reported for penguins, two elasmobranchs, and the harbor seal (Lorrain et al ; Dale et al ; Germain et al ; Hoen et al ; McMahon et al ,b). TP estimates from our study support the contention of previous work that a TDF of 7.6‰, based on Chikaraishi et al (), is adequate only for species with TPs < 3.0 (Chikaraishi et al ; Hannides et al ; Dale et al ; Germain et al ; Bradley et al ). We empirically estimated TDF values using the methodology of Bradley et al () and found decreasing TDF values with increasing TPs.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Underestimated TPs based on CSIA‐AA have also been reported for penguins, two elasmobranchs, and the harbor seal (Lorrain et al ; Dale et al ; Germain et al ; Hoen et al ; McMahon et al ,b). TP estimates from our study support the contention of previous work that a TDF of 7.6‰, based on Chikaraishi et al (), is adequate only for species with TPs < 3.0 (Chikaraishi et al ; Hannides et al ; Dale et al ; Germain et al ; Bradley et al ). We empirically estimated TDF values using the methodology of Bradley et al () and found decreasing TDF values with increasing TPs.…”
Section: Discussionmentioning
confidence: 79%
“…Amino acids were grouped into two categories, trophic amino acids: alanine (Ala), aspartic acid (Asp), glutamic acid (Glu), leucine (Leu), and proline (Pro); and source amino acids: glycine (Gly), lysine (Lys), phenlyalanine (Phe), serine (Ser), and threonine (Thr). Since Thr values are extremely negative relative to other source AAs, we recognize that including Thr as a source AA may not be appropriate and recent studies are classifying Thr as a “metabolic” amino acid (Germain et al ; Bradley et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This calculation was derived largely from experimental studies on invertebrates and fish, and recent studies have suggested that a TEF Glu-Phe of 7.6‰ results in lower than anticipated trophic position estimates of higher marine consumers (Lorrain et al, 2009;Dale et al, 2011), including marine mammals (Germain et al, 2013). Given equation (1) Best-fit generalized linear mixed effects models indicated GLG (age) was a significant predictor of d 15 N values (P , 0.005), but not d 13 C cor values (P .…”
Section: Aa-specific D 15 N--baseline D 15 N and Trophic Position Indmentioning
confidence: 99%
“…This allowed them to estimate trophic levels for zooplankton and other consumers, and to derive the δ 15 N of basal resources. However, the trophic enrichment between glutamic acid and phenylalanine appears to be different for herbivory (plant-animal; 7.6 ‰) and carnivory (animalanimal; 4.3‰), complicating inferences based on compoundspecific δ 15 N analysis (Germain et al, 2013). Basal resources δ 15 N values are notoriously difficult to obtain because of high temporal variability due to intense recycling and assimilation of dissolved inorganic nitrogen by heterotrophic bacteria (Kirchman, 1994;Veuger et al, 2005).…”
Section: Compound Specific Isotope Analysis Allows Including Microbiamentioning
confidence: 99%